Simulation study of the effect of electrode embedded with magnesia-carbon material on the breakdown process in micro-gap and electric field in arc. (1st December 2022) - Yan, Zhaozhao; Zhang, Jiongming; Liu, Qiang; Yin, Yanbin; Ma, Haitao; Liu, Huayang
Abstract: The breakdown plays an important role in the process of arc striking, which can form an early conductive channel between electrode and molten pool. In this paper, a two-dimensional transient micro-gap breakdown model of argon gas under atmospheric pressure and a two-dimensional calculation model of electric field in arc were established, and the effect of the electrode embedded with magnesia-carbon material on the breakdown process and electric field in arc are studied. It is found that the breakdown process between the electrode and the molten pool develops in the form of positive streamer, whether using ordinary electrode or electrode embedded with magnesia-carbon material. The electrode embedded with magnesia-carbon material can accelerate the development of head of electron avalanche in the process of breakdown in micro-gap, increase the electron density of head of electron avalanche and shorten the time consumed in the process of breakdown. Under the external voltage in AC arc, the maximum value of electric field strength changes periodically, the region of the maximum value and maximum value increases with the increase of the radius of the magnesia-carbon material, resulting in serious distortion in the distribution of electric field, which can effectively reduce the breakdown voltage threshold.